Name the property of step 1 in the following equation

6x - 5 = 7
6x - 5 + 5 = 7 + 5 (step 1)
6x = 12
6x/6 = 12/6 (step 2)
x = 2
*
1 point
Addition property of equality
subtraction property of equality
division property of equality
multiplication property of equality
Solve the equation
5x - 14 = 21
*
1 point
x = 35
x = 7
x = 7/5
x = 175
Which value of x makes the equation true?
80 - 2x = 100
*
1 point
x = 60
x = -60
x = 10
x = -10
Solve for x
x/3 + 63 = 60
*
1 point
x = 369
x = -9
x = 41
x = -1
What is the solution?
87 = 4x + 35
*
1 point
x = 30.5
x = 52
x = 13
x = 208

1 answer

Let’s go through each question one by one:

  1. Name the property of step 1 in the following equation:

    • 6x - 5 = 7
    • 6x - 5 + 5 = 7 + 5 (step 1)

    The property used here is the Addition property of equality.

  2. Solve the equation:

    • 5x - 14 = 21

    To solve for x: \[ 5x - 14 + 14 = 21 + 14 \implies 5x = 35 \] \[ x = \frac{35}{5} = 7 \]

    So, the answer is x = 7.

  3. Which value of x makes the equation true?

    • 80 - 2x = 100

    Rearranging gives: \[ -2x = 100 - 80 \implies -2x = 20 \] Dividing by -2: \[ x = \frac{20}{-2} = -10 \]

    So, the answer is x = -10.

  4. Solve for x:

    • x/3 + 63 = 60

    To solve for x: \[ x/3 = 60 - 63 \implies x/3 = -3 \] Multiplying both sides by 3: \[ x = -3 \times 3 = -9 \]

    So, the answer is x = -9.

  5. What is the solution?

    • 87 = 4x + 35

    To solve for x: \[ 87 - 35 = 4x \implies 52 = 4x \] Dividing by 4: \[ x = \frac{52}{4} = 13 \]

    So, the answer is x = 13.

To summarize:

  1. Addition property of equality
  2. x = 7
  3. x = -10
  4. x = -9
  5. x = 13
Similar Questions
  1. Order the steps for solving the equation:   2x−5=3(4x+5)(8 points) 2x−5=3(4x+5) Step 1: Property to get Step 2: Property
    1. answers icon 1 answer
  2. Is this correctOrder the steps for solving the equation: 2x−5=3(4x+5) (8 points) 2x−5=3(4x+5) Step 1: Distributive Property
    1. answers icon 3 answers
    1. answers icon 1 answer
  3. Consider the sequence of steps to solve the equation:5(x - 3) = 7x2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 3 answers
more similar questions